Implementing Sharia Finance as an Alternative to Address Economic Vulnerability and Social Justice - Widayati, Catur (Journal International Economic Sharia, 2024)
Objective; This study examines the effect of ESG on stock price and EPS as a moderating variable mining. We look at the impact of ESG on market performance but pay extra attention to the moderating impact of EPS on the relationship between ESG and stock priceMethods; Data were collected quantitatively through purposive sampling of 140 mining companies, incorporating ESG scores and idx stock prices. com, EPS from MarketWatch.co.id, and EPS from MarketWatch. The validity and reliability of the findings were determined by performing classical assumption tests, as well as a multiple regression analysis.Results; Analysis indicates there is a significant relationship of ESG scores and stock prices and EPS moderate the relationship between both. These findings emphasize the effect of individual ESG dimensions on investors' behaviours and market pricing, suggesting that positive ESG characteristics improve shares valuation, moderated by EPS.Novelty; The current literature lacks empirical investigations of the effects of both ESG scores and EPS on stock prices in the mining sector. The use of EPS as a moderator offer further understanding of how financial performance may make a difference regarding stock holders' responses to ESG disclosures.Research Implications; There are important implications from these findings for policymakers, investors, and corporate managers. It highlights the need to incorporate ESG factors into both investment decisions and corporate governance practices, also emphasizes the significance of EPS in influencing market perceptions and actions.